Emphysematous pyelonephritis – case report and review of literature - Ćelić, Dejan; Božić, Dušan; Petrović, Kosta; Živojinov, Srđan; Đurđević Mirković, Tatjana; Popović, Milica (Vojnosanitetski pregled, 2018)
Introduction. Emphysematous pyelonephritis (EPN) is a severe, potentially fatal necrotizing infection of the kidney with the clinical picture ranging from the mild abdominal pain and discomfort to the septic shock and multiorgan failure. We presented here a case of EPN in a poorly controlled diabetic patient that was the first registered case of EPN in our clinic for more than ten years. Case report. A 78-year-old diabetic male patient was referred to the Clinic for Nephrology and Clinical Immunology of the Clinical Center of Vojvodina, Novi Sad, Serbia, with weakness, malaise, abdominal discomfort and reduced daily urine volume. After complete physical exam, laboratory work up, echosonographic and computed tomography scanning we diagnosed the patient with EPN class IV, according to the Huang and Tseng classification, with the presence of 5 risk factors for mortality (systolic blood pressure below 90 mmHg, altered consciousness, thrombocytopenia, elevated serum creatinine level, bilateral disease). Treatment with conservative therapy and percutaneous drainage was not successful, further deteorioration of the patient status ensued so the patient passed away on the 8th day of hospitalization due to the development of septic shock with multiorgan failure that was refractory to all measures that were instituted. Conclusion. EPN is a severe, potentially fatal necrotizing inflammation of the kidney and surrounding tissue. Management and prognosis of this disease depends on the clinical status, risk factors and radiological classification of the disease.